Development of Integrated PowerPoint-iSpring Learning Media Prompting Questions on Compound Nomenclature Material for Class X SMA/MA - Danisyah Melga; Guspatni Guspatni (Universitas Negeri Padang, 2022)
Education today demands student-centered learning. With the PowerPoint-iSpring learning media containing prompting questions, it helps students find the concept of a material so that students can play an active role in learning. With the advantages of this learning media, students can learn independently wherever and whenever. PowerPoint-iSpring learning media uses a trigger feature that provides feedback when students answer true/false on the prompting questions that have been provided. This study aims to develop integrated PowerPoint-iSpring learning media Prompting Questions on Compound Nomenclature Material for Class X SMA/MA and determine the level of validity of the developed media. This study uses the Plomp research model to be carried out until prototype 3 (one to one evaluation and expert review). The subjects in the study were chemistry lecturers at FMIPA UNP and SMAN 1 Painan teachers as material expert validators, FT UNP engineering lecturers as media expert validators, and class X and XI students at SMAN 1 Painan for the 2020/2021 academic year. The instruments used in this study were validation questionnaires (for material experts and media experts) and interview sheets. The results of the experimental data processing of the validity test using the Aiken's V formula showed that the PowerPoint-iSpring learning media integrated prompting questions on the compound nomenclature material developed was valid for each item on the content, construct, and media components.